Eric R. Dursteler, Renegade Women: Gender, Identity and Boundaries in the Early Modern Mediterranean, Βαλτιμόρη 2011 / Gillian Weiss, Captives and Corsairs: France and Slavery in the Early Modern Mediterranean, Stanford CA, 2011 - ΠΛΑΚΩΤΟΣ, ΓΙΩΡΓΟΣ (Μνήμων, 2012)
Δεν παρατίθεται περίληψη.